Mental Health in the Workplace: A Call to Action Proceedings From the Mental Health in the Workplace—Public Health Summit. Issue 4 (April 2018) - Goetzel, Ron Z.; Roemer, Enid Chung; Holingue, Calliope; Fallin, M. Daniele; McCleary, Katherine; Eaton, William; Agnew, Jacqueline; Azocar, Francisca; Ballard, David; Bartlett, John; Braga, Michael; Conway, Heidi; et al.
Abstract : Objective: The aim of the study was to declare a call to action to improve mental health in the workplace. Methods: We convened a public health summit and assembled an Advisory Council consisting of experts in the field of occupational health and safety, workplace wellness, and public policy to offer recommendations for action steps to improve health and well-being of workers. Results: The Advisory Council narrowed the list of ideas to four priority projects. Conclusions: The recommendations for action include developing a mental health in the workplace (1) "how to" guide, (2) scorecard, (3) recognition program, and (4) executive training.